Correction: On the stability of manganese tris(β-diketonate) complexes as redox mediators in DSSCs. Issue 19 (3rd May 2016) - Carli, Stefano; Benazzi, Elisabetta; Casarin, Laura; Bernardi, Tatiana; Bertolasi, Valerio; Argazzi, Roberto; Caramori, Stefano; Bignozzi, Carlo Alberto
Abstract : Correction for 'On the stability of manganese tris(β-diketonate) complexes as redox mediators in DSSCs' by Stefano Carli et al., Phys. Chem. Chem. Phys., 2016, 18, 5949–5956.